Mediating effect of psychological safety on the relationship between inclusive leadership and nurses’ absenteeism - Ayman Mohamed El-Ashry; Bashair Mohamed Elsayed Abdo; Mahmoud Abdelwahab Khedr; Mona Metwally El-Sayed; Islam Sameh Abdelhay; Mennat-Allah G. Abou Zeid (BMC Nursing)
Abstract Objective This study aimed to investigate the mediating role of psychological safety in the relationship between inclusive leadership and implicit absenteeism among nurses. Design A descriptive, correlational cross-sectional design was conducted in accordance with the STROBE guidelines. Methods Data were collected from 407 nurses working in two public hospitals in El-Behara Governorate, Egypt, using validated Arabic versions of the Inclusive Leadership Scale, Psychological Safety Scale, and the Stanford Presenteeism Scale (SPS-6). Descriptive statistics, Pearson’s correlations, multiple regression, and structural equation modeling (SEM) were employed to analyze the data using SPSS and AMOS (version 26). Results Inclusive leadership was significantly and negatively associated with implicit absenteeism (r = − 0.207, p = 0.030) and positively associated with psychological safety (r = 0.204, p = 0.036). Psychological safety was also negatively correlated with implicit absenteeism (r = − 0.202, p = 0.041). Regression analysis revealed that both inclusive leadership (β = − 0.098, p = 0.049) and psychological safety (β = − 0.091, p = 0.048) significantly predicted lower implicit absenteeism. Furthermore, SEM results confirmed that psychological safety partially mediated the relationship between inclusive leadership and implicit absenteeism (indirect effect β = − 0.010). The model demonstrated an acceptable fit (RMSEA = 0.091; CFI = 1.000; IFI = 1.000; χ² = 9.748, p < 0.001). Conclusion The findings highlight the critical role of inclusive leadership in reducing implicit absenteeism by fostering psychological safety. Promoting inclusive leadership practices and psychologically safe work environments may enhance nurse engagement, reduce presenteeism-related productivity loss, and ultimately improve patient care outcomes. Clinical trial registration Not applicable.